Kegiatan Komunikasi Pemasaran Dalam Meningkatkan Brand Awareness di Kota Semarang - Vitadila, Angelina Loren; Vanel, Zon (Jurnal Pustaka Komunikasi, 2024)
MG Setos Hotel Semarang is facing a variety of obstacles to survive in the midst of the new normal conditions induced by the COVID-19 epidemic. Travel constraints, health concerns, and social isolation have all contributed to a considerable drop in overnight visitors. This has the potential to damage the hotel's revenue and financial stability. Hotels must maintain a high level of service and visitor experience despite current constraints. A hotel's reputation can benefit from providing good service throughout the new normal. As a result, it is critical for the management of MG Setos Hotel Semarang to plan ahead of time and innovate in order to address the challenges that have arisen. The purpose of this study is to determine how MGSetos Hotel Semarang can boost brand recognition by using the Integrated Marketing Communication (IMC) approach. This study employs qualitative research methods such as interviews, observations, and documentation to acquire data. The triangulation of sources, procedures, and time ensures the veracity of the data employed. According to the research findings, MGSetos Hotel Semarang has created an integrated marketing communication plan to improve brand awareness, however its implementation has been subpar. Using this method can raise hotel brand awareness in the community even if it is not presently at the forefront of people's minds. This study has substantial practical implications for hospitality firms operating in unpredictable times.